Application of Psychological Autopsy: A Study Case of two Suicides in a Family - Valdés García, Karla Patricia (Consorcio de Universidades Mexicanas A.C., 2021)
Suicide is a deliberate and complex act that can occur due to various factors. The objective of this research was to reconstruct the psychosocial factors associated with the suicide of two family members using a qualitative approach to psychological autopsies. The mother of the deceased was interviewed regarding the precipitating factors, motivation, lethality, and intentionality of the cases. The results identified the presence of precipitants and motivators associated with love difficulties. As the method was hanging, lethality and intentionality were high. Additionally, previous suicidal ideation was documented in one case. It is concluded that couple relationships, and ruptures within them, seemed to be a significant factor, that suicides in a family generate vulnerability in its members to present suicidal behaviors, and that risk factors should continue to be studied to develop effective preventive strategies.